(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
In this article In Uzbekistan village farm products work to release volume in 2009–2024 dynamics timely row information based on timely the train economic -mathematical modeling through the trend determination for the purpose of striped and exponential trend models developed . Received results village farm products work to release in volume stable growth trend the existence showed .